1992
DOI: 10.1073/pnas.89.24.11925
|View full text |Cite
|
Sign up to set email alerts
|

DNA strand-specific repair of (+-)-3 alpha,4 beta-dihydroxy-1 alpha,2 alpha-epoxy-1,2,3,4-tetrahydrobenzo[c]phenanthrene adducts in the hamster dihydrofolate reductase gene.

Abstract: We evaluated the formation and removal of (+)-3a,48-dihydroxy-la,2a-epoxy-1,2,3,4-tetrahydroben- 2). A similar strand bias for BPDE-induced mutations in the hypoxanthine phosphoribosyl transferase gene (HPRT) of human fibroblasts was described where 77% of the premutagenic guanine bases were also on this strand (3). Assuming that carcinogen modification of DNA in vivo occurs with similar frequency on both strands, several possible explanations for the apparent strand selectivity of induced mutations can be co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 35 publications
0
15
0
Order By: Relevance
“…EMS mainly induces GC to AT transitions (2), and BcPHDE induces purine-to-T transversions in mammalian cells (10). Perusal of the substrate sequences (Table 2) shows that if fixation of induced mutations occurs preferentially on the nontranscribed strand (5,12), this mutagen action could account for much of the specificity, since there are no G or A substitutions that would improve the splice donors at positions +3, +4, +5, and +6. Changes in the exonic positions -1, -2, and -3 are obviously constrained by the necessity to effect nondetrimental amino acid changes in the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…EMS mainly induces GC to AT transitions (2), and BcPHDE induces purine-to-T transversions in mammalian cells (10). Perusal of the substrate sequences (Table 2) shows that if fixation of induced mutations occurs preferentially on the nontranscribed strand (5,12), this mutagen action could account for much of the specificity, since there are no G or A substitutions that would improve the splice donors at positions +3, +4, +5, and +6. Changes in the exonic positions -1, -2, and -3 are obviously constrained by the necessity to effect nondetrimental amino acid changes in the enzyme.…”
Section: Methodsmentioning
confidence: 99%
“…There is reason to believe that strand-independent repair mechanisms may also serve a biological function-to maintain genetic stability rather than to promote cellular survival. Recent studies in rodent cells have shown that selectively repaired genes (template strand restricted) can be readily mutagenized by an accumulation of premutagenic lesions in the poorly repaired, nontemplate strand (8,18,36 phoblasts demonstrates a consistent correlation between repair deficiency and translocation breaksite regions.…”
Section: Methodsmentioning
confidence: 99%
“…The effects of trans-anti-[BPh]-N 6 -dA adducts on RNA polymerase II elongation is of particular interest because these lesions are poor substrates for NER, leaving TCR as an important pathway for their removal (26,45). (+)-1R-and (±)-1S-trans-anti-[BPh]-N 6 -dA lesions induce relatively less perturbations to double-stranded DNA compared with the analogous adducts derived from benzo[a]pyrene (46); this fact, coupled with the absence of damaged duplex destabilization and optimized stacking of the stereoisomeric adducts with the DNA, explains why NER recognizes these lesions poorly when they are present in the genome (46,47).…”
Section: The (+)-1r-and (±)-1s-trans-anti-[bph]mentioning
confidence: 99%
“…Little is known about the behavior of human RNA polymerase II at BPhDE lesions in DNA. Considering that there is a strand bias in mutagenesis for BPhDE adducts in DNA (15) that may well result from TCR operating on these lesions (26), it was of interest to assess the behavior of RNA polymerase II during transcription elongation past BPhDE lesions in DNA.…”
Section: Introductionmentioning
confidence: 99%